Kajian lapis perkerasan dan kerusakan jalan pada proyek rekontruksi jalan ruas batas Provinsi Sulteng – Lamonae – Landawe - Alifuddin, Andi; Alifuddin, Andi Nurfadillah; Massara, Asma (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
The Central Sulawesi – Lamonae – Landawe border section is designated as a national route that links the Southeast Sulawesi region with Central Sulawesi, specifically the mining industrial district of Morowali City. This route facilitates not only community mobilization but also the transportation of heavy mining equipment. Daily, the road endures heavy vehicle traffic carrying logistics, which increases the volume and load on this route, leading to pavement layer damage and a decline in service quality. This study aims to analyze the road surface conditions and determine the appropriate handling program using the Surface Distress Index (SDI) and International Roughness Index (IRI) methods, spanning from STA 0+000 to STA 5+500 over a segment length of 5.5 km. Subsequently, it plans the pavement layer thickness design for segments with severe surface damage using the 2017 Pavement Design Manual. The study results indicate that, according to the SDI method, 47% of the road is in good condition, 24% in moderate condition, 16% in minor damage, and 13% in severe damage. According to the IRI method, 27% of the road is in good condition, 49% in moderate condition, 15% in minor damage, and 9% in severe damage. Based on SDI and IRI values, a handling program comprising routine maintenance, periodic maintenance, and reconstruction is established. The pavement layer thickness calculation, based on the 2017 Pavement Design Manual, recommends asphalt pavement with granular base layers, comprising AC WC with a thickness of 40 mm, AC BC with 60 mm, AC Base with 80 mm, and Class A Granular Base with a thickness of 300 mm, along with subgrade improvement with a planned thickness of 200 mm.